Preliminary study on sex-related inflammatory reactions in mice infected with Schistosoma mansoni - Boissier, Jérôme; Chlichlia, Katerina; Digon, Y.; Ruppel, Andreas; Moné, H. (Parasitology research, 2003)
The aim of this study was to investigate the contribution of the sex of both the parasite and the host to the inflammatory response induced in unisexual infections of Schistosoma mansoni in mice. Organ weight, cell count and the delayed type hypersensitivity reaction were used as tools in this comparative study. The inflammatory reactions differed as a function of the sex of both the host and the parasite. Female mice showed a stronger inflammatory reaction to schistosome infection than males, while male schistosomes induced a stronger inflammatory response compared to females. The host-related differences in the inflammatory reaction may reflect differences in the factors affecting the immune defence of male and female mice. The differences in the inflammatory response induced by the parasite are discussed in terms of the quantity and quality of antigens among male and female worms.
Gesehen am 14.04.2021